Perceived changes in the knowledge and confidence of doctors and midwives to manage obstetric emergencies following completion of an Advanced Life Support in Obstetrics course in Australia - Walker, Laura; Fetherston, C.; McMurray, A. (Wiley-Blackwell Publishing Asia, 2013)
Background: The Advanced Life Support in Obstetrics (ALSO) course is an internationally recognised interprofessional course to support health professionals to develop and maintain the knowledge and skills to manage obstetric emergencies. Aims: This study investigated changes in confidence and perceived changes in the knowledge of doctors and midwives to manage specific obstetric emergency situations following completion of an ALSO course in Australia. Methods: A prospective repeated-measures survey design was used to survey 165 course attendees from four Australian states pre- and postcourse and at six weeks (n = 101). Data were analysed using a Friedman two-way repeated-measures analysis of variance and the Wilcoxon signed rank test. Results: There was a significant improvement in confidence and perceived knowledge of the recommended management of all 17 emergency situations immediately postcourse (P < 0.001) and at six weeks postcourse (P < 0.001) when compared to precourse levels for both groups of health professionals. However, a significant decrease in knowledge and confidence for many emergency situations from immediately postcourse to six weeks postcourse (P < 0.05) was also observed in both groups. Conclusions: Completion of the Australian ALSO course in Australia has a positive effect on the confidence and perceived knowledge of doctors and midwives to manage obstetric emergencies. However, there needs to be some means of reinforcing the effects of the course for longer term maintenance of knowledge and confidence.